STATISTIKA DESKRIPTIF SEBAGAI KUMPULAN INFORMASI - Lilih Deva Martias (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2021)
A descriptive statistic is one of the statistical analytic tools that very famous to present any data. A descriptive statistic usually used as the first step to tidying up the data before we continue to the next analysis. Therefore, a descriptive statistic may stand as an independent analysis that can present data and give some information about data. There are so many descriptive forms that can be made from any data. Start with the visual form like table, chart, or any data measurement like a measure of central tendency, a measure of the place value, and a measure of dispersion. Many kinds of data can be present as descriptive therefore not every description contain a piece of optimal information for a certain data. The word optimal here means that the descriptive form may give information to estimate population data or to make a decision to follow up any policy. For examples in digital library visitors, the descriptive forms that are very useful are table, chart, and measure of central tendency. While the other measurement will more suitable for other data like the usability of the collection. From this case, so it must be scrutinized what information do we hope for before we decide what kinds of descriptive form will be made.